Design, delivery, and determinants of uptake: findings from a food hygiene behavior change intervention in rural Bangladesh - Sobhan, Shafinaz; Müller-Hauser, Anna A.; Huda, Tarique Md. Nurul; Waid, Jillian; Gautam, Om Prasad; Gon, Giorgia; Wendt, Amanda; Gabrysch, Sabine (BMC public health, 2022)
Microbial food contamination, although a known contributor to diarrheal disease and highly prevalent in low-income settings, has received relatively little attention in nutrition programs. Therefore, to address the critical pathway from food contamination to infection to child undernutrition, we adapted and integrated an innovative food hygiene intervention into a large-scale nutrition-sensitive agriculture trial in rural Bangladesh. In this article, we describe the intervention, analyze participation and uptake of the promoted food hygiene behaviors among intervention households, and examine the underlying determinants of behavior adoption.